Analysis of the different physical mechanisms in the atypical sporadic E (Es) layer occurrence over a low latitude region in the Brazilian sector - Resende, L. C. A.; Zhu, Y.; Denardini, C. M.; Chagas, R. A. J.; Da Silva, L. A.; Andrioli, V. F.; Figueiredo, C. A. O.; Marchezi, J. P.; Chen, S. S.; Moro, J.; Silva, R. P.; Li, H.; et al. (Frontiers in Astronomy and Space Sciences, 2023)
We present a study about the atypical and spreading Sporadic E-layers (Es) observed in Digisonde data. We analyzed a set of days around space weather events from 2016 to 2018 over Cachoeira Paulista (CXP, 22.41°S, 45°W, dip ~35°), a low-latitude Brazilian station. The inhomogeneous Es layer is associated with the auroral-type Es layer (Esa) occurrence in this region due to the presence of South American Magnetic Anomaly (SAMA). However, we also observe that the spreading Es layers occurred days before the magnetic storms or quiet times. Also, this specific type of Es layer has some different characteristics concerning the Esa layer. We used data from the imager, satellite, and meteor radar to understand the dynamic processes acting in this Es layer formation. Our results lead us to believe that other mechanisms affect the Es layer development. We show evidence that the instabilities added to the wind shear mechanism can cause the atypical Es layers, such as Kelvin-Helmholtz instability (KHI). Finally, an important discovery of this work is that the spreading Es layer, mainly during quiet times, is not necessarily due to the particle precipitation due to the SAMA. We found that the wind shear can be turbulent, influencing the Es layer development. Lastly, our analysis better understood the Es layer behavior during quiet and disturbed times.